Improving productivity through line balancing : a case study - Lim, Chuan Pei (Faculty of Mechanical Engineering, 2002)
This paper describes a case study conducted at a manufacturing company aimed at improving productivity using line balancing. Two alternatives were generated using different assignment rules. However selection of the most suitable alternatives cannot be made based on line balancing alone as they appear similar based on line balance loss. Thus the robustness of the alternatives were tested and evaluated using a 16 factorial ANOVA. Selection of the most suitable solution is then made based on these results.